Energy Landscapes: Applications to Clusters, Biomolecules and Glasses - David Wales (Cambridge Molecular Science, 2004)
This book aims to provide a self-contained account of energy landscape theory and how it is used in studies of clusters, biomolecules and glasses. Many groups are now attempting to understand how the properties of systems ranging from small molecules to proteins and glasses are determined by the energy landscape. This is the first book to cover this active field. Beautifully illustrated in full colour throughout it is aimed at graduate students and workers in the field.